Impact of physical exercise/activity on vascular structure and inflammation in pediatric populations: A literature review - Cayres, Suziane Ungari [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; de Moura Mello Antunes, Barbara [UNESP]; Lira, Fabio Santos [UNESP]; Fernandes, Rômulo Araújo [UNESP] (Wiley, 2016)
Purpose: To describe the effects of physical exercise/activity on the vascular architecture of children and adolescents, as well as to identify the effects of inflammation and sedentary behaviors on this relationship. Methods: Potentially relevant articles were identified in the databases MEDLINE and PubMed covering the period from 2000 to 2015. No language restrictions were applied. Results: Thirteen articles were found that included obese boys and girls in their samples (aged 9–19). Six interventional studies assessed inflammation and in five of these, physical exercise decreased inflammation. In 10 studies, vascular architecture was affected by physical exercise/activity. Conclusions: The impact of physical exercise on vascular architecture and inflammation seems relevant, but has been mainly investigated in obese groups. Practical Implications: Health professionals should act together in organized interventions in schools, targeting the promotion of higher physical activity levels in children and adolescents.
Keywords: Adolescent; arterial pressure; carotid intima–media thickness; inflammation; motor activity